Speeding up the brain: when spatial facilitation translates into latency shortening - Paradis, Anne-Lise; Morel, Shasha; Seriès, Peggy; Lorenceau, Jean (Frontiers in Human Neuroscience, 2012)
Waves of activity following a focal stimulation are reliably observed to spread across the cortical tissue. The origin of these waves remains unclear and the underlying mechanisms and function are still debated. In this study, we ask whether waves of activity modulate the MEG signals recorded in humans during visual stimulation with Gabor patches sequentially flashed along a vertical path, eliciting a perception of vertical apparent motion. Building upon the functional properties of long-rang horizontal connections, proposed to contribute to spreading activity, we specifically probe the amplitude and latency of MEG responses as a function of Gabor contrast and orientation. The results indicate that the response amplitude is enhanced and the response latency is shortened for co-aligned Gabor as compared to misaligned Gabor patches at a low but not at a high contrast. Building upon these findings, we develop a biologically plausible computational model that performs a ‘spike time alignment’ of the responses to elongated contours with varying contrast, endowing them with a phase advance relative to misaligned contours.